Two-photon imaging of chronically implanted neural electrodes: Sealing methods and new insights - Kozai, Takashi D. Y. (J Neurosci Methods, 2015)
BACKGROUND: Two-photon microscopy has enabled the visualization of dynamic tissue changes to injury and disease in vivo. While this technique has provided powerful new information, in vivo two-photon chronic imaging around tethered cortical implants, such as microelectrodes or neural probes, present unique challenges. NEW METHOD: A number of strategies are described to prepare a cranial window to longitudinally observe the impact of neural probes on brain tissue and vasculature for up to 3 months. RESULTS: It was found that silastic sealants limit cell infiltration into the craniotomy, thereby limiting light scattering and preserving window clarity over time. In contrast, low concentration hydrogel sealants failed to prevent cell infiltration and their use at high concentration displaced brain tissue and disrupted probe performance. COMPARISON WITH EXISTING METHOD(S): The use of silastic sealants allows for a suitable imaging window for long term chronic experiments and revealed new insights regarding the dynamic leukocyte response around implants and the nature of chronic BBB leakage in the sub-dural space. CONCLUSION: The presented method provides a valuable tool for evaluating the chronic inflammatory response and the performance of emerging implantable neural technologies.